Growth in the Economic and Hydraulic Engineering Capacities Drives Water Quality Improvement in the Eastern Region of Nansi Lake, China - Zhao, Yuhang; Wu, Shiqiang; Dai, Jiangyu; Wu, Xiufeng; Zhang, Yu; Yang, Rui; Wu, Chenhui; Feng, Kedong (Frontiers in Environmental Science, 2022)
Knowledge of the extent of water pollution along a diversion channel is essential for ensuring the security and effectiveness of water diversion projects. Thus, identifying the trends in the water quality and the factors which influence the trends along a diverted river is a prerequisite to ensuring the safety of the water diversion. As an important control unit of the Eastern Route of the South to North Water Diversion Project, the hilly eastern region of Nansi Lake Basin (ENLB) suffers excess water pollution in the water transferred into Nansi Lake during the flood season. The comprehensive pollution index (CPI), the Mann-Kendall trend test and analysis of variances were used to characterize the spatiotemporal variation of water quality in the three main mountainous rivers of the ENLB. The contribution of different factors which influencing the variation of the water quality parameters may be explained using ridge regression analysis. The results showed that the CPI for the three major rivers decreased significantly from 2000 to 2012. The rivers had problems in compliance, and this was most noticeable in the Guangfu River. The main pollutants exceeding the water quality standards were the chemical oxygen demand and total phosphorus. The GDP per capita was the largest factor which influenced the changes in the regional water quality, with the average contribution being 30%. An increase in the water storage capacity was shown to have a positive effect on improving the water quality. The results provided a scientific basis for establishing a regional pollution control strategy and would give support to the planning of future water diversion projects.